Review of immunological methods for the quantification of aflatoxins in peanut and other foods - Waliyar, Farid; Reddy, S.V.; Kumar, P. Lava (2009)
Aflatoxin contamination is widespread instaple crops like peanut, maize, sorghum, pearlmillet, chillies, pistachio, cassava etc., and com-promises the safety of food and feed supplies. It isimportant to be able to detect and quantifyaflatoxins in commodities to protect human andanimal health. Many different methods, includingantibody-based ones, are available for quantita-tive estimation of aflatoxins. However, most ofthese methods such as HPLC, HPTLC, and TLCare expensive and/or difficult to use in developedcountries. Using the state-of-the-art facilities atICRISAT, we developed polyclonal and mono-clonal antibodies for the detection of totalaflatoxins, aflatoxin B1 and M1 (secreted in milk).These were used to develop a simple andinexpensive competitive enzyme-linked immuno-sorbent assays (cELISA) that has lower detectionlimits (1.0mg/kg) and cost (about $1 per sample)less than other available methods. More than 100samples can be analyzed in a day. These tests haveprovided a unique opportunity for ICRISAT andits partners to conduct field studies to selectresistant genotypes, identify high risk populationsand determine the dietary sources to stimulateappropriate interventions to enhance the food andhuman health safety, trade and thereby farmers’income